Overweight and obesity amongst Black women in Durban, KwaZulu-Natal: A 'disease' of perception in an area of high HIV prevalence - Rynal Devanathan; Tonya M. Esterhuizen; Romona D. Govender (AOSIS, 2013)
Background: Overweight and obesity is an emerging health problem, particularly amongst urban Black women living in areas of high HIV prevalence. Understanding factors affecting this pandemic is essential to enable effective weight loss programmes to be implemented. This study explored urban Black women's perception of their body image against a backdrop of pre-existing non-communicable diseases (NCDs). Method: In this cross-sectional exploratory study 328 urban Black women were sampled systematically. Anthropometric measurements were conducted and women were interviewed using the Stunkard body image silhouettes as a tool to determine perception. Results: Most of the subjects (61%) were in the 40-59 years age group. Mean body mass index (BMI) was 37 (± 9.41 kg/m2) with over 90% being overweight or obese. Diabetes mellitus was the most common NCD, with a prevalence of 72%. Amongst the diabetic patients 7% were overweight and 64% obese. Perceived body image compared to derived BMI showed that women underestimated their body image across all weight categories. Over 40% indicated a normal to overweight preferred body image, with 99% of respondents associating the underweight silhouettes with disease and HIV infection. Conclusion: Urban Black women with underlying NCDs and living in an area of high HIV prevalence perceive themselves to be thinner than their actual BMI, which may be a barrier to weight loss management. This misperception may be used as a proxy risk marker for weight gain in urban Black women.